Characteristics of Financial Technology as Financing Alternative Capitalization of Medium Small-Medium Enterprises (MSME) - Dwi Tatak Subagiyo (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
Characteristics of Financial Technology as a Financial Institution that uses information technology to provide financial solutions by prioritizing compliance with the principles of prudence and risk management. The characteristics of Financial Technology institutions are getting a loan quickly; Makes Payment Easier; Make Loan Payments without Additional Fees. Peer to Peer Lending (P2P lending) system in providing financial services is done through information technology based. The financial services institution Peer to Peer Lending (P2P Lending) is a financial technology financial institution (Fintech). Financial Technology (Fintech) as a Literacy Source for Financing Micro, Small and Medium Enterprises; Financial Technology (Fintech) As a Facilitator in MSME Development; Financial Tecnology (Fintech) as a driver for Micro, Small and Medium Enterprises to Increase National Financial Inclusion. The Role of the Financial Services Authority (OJK) and the Indonesian Joint Funding Fintech Association (AFPI) As Regulations and Oversight of Financial Technology Institutions (Fintech) in Indonesia.